P024 PATIENT AND HEALTHCARE PROVIDER VIEWS ON ULCERATIVE COLITIS TREATMENT GOALS AND QUALITY OF LIFE: RESULTS OF A GLOBAL ULCERATIVE COLITIS NARRATIVE SURVEY. (7th February 2019) - Dubinsky, Marla; Panaccione, Remo; Lopez-Sanroman, Antonio; Watanabe, Kenji; Rubin, David T; Peyrin-Biroulet, Laurent; Melmed, Gil; Rubin, Michele; Keefer, Laurie; Colombel, Jean-Frederic; Kayhan, Cem
Abstract: Objective: The Ulcerative Colitis (UC) Narrative is a global survey of patients (pts) and gastroenterology physicians (GIs) aimed at identifying the impact of UC and comparing and contrasting perceptions of UC burden and management approaches. Here, we focus on pt and GI expectations of UC management and establishing treatment goals, and present data from 2100 pts and 1254 GIs in Australia, Canada, Finland, France, Germany, Italy, Japan, Spain, the UK, and the USA. Methods: Surveys were conducted online and by phone by The Harris Poll between August 2017 and February 2018. Adult pts with UC (confirmed by endoscopy) who had visited a GI in the previous 12 months and had ever received prescription medication for UC were eligible for inclusion. Self-reported medication history was used as a proxy for disease severity. Pts with moderate to severe UC were those who had ever taken immunosuppressants, tumor necrosis factor inhibitors, other biologics, or corticosteroids for >4 of the past 12 months. Pts who had only ever taken 5-aminosalicylates or had a colectomy were excluded. Eligible GIs were those who saw ≥10 UC pts each month (≥5 in Japan), of whom ≥10% were taking a biologic and did not practice in a long-term care facility or hospice. Data are presented from all respondents who consented and completed the survey. Results: Pts had a mean age of 40.8 (standard deviation [SD] 12.4) years and 53% were male. Most pts (82%) had moderate to severe UC and 67% described their UC as being controlled with few to no symptoms. GIs had been in specialty practice for a mean of 16.4 (SD 8.4) years and saw a mean of 40 pts with UC each month. Most pts (65%) felt that UC controlled their life rather than them controlling their disease, including significant time spent in the bathroom, with 67% feeling that they spend more time in the bathroom than anywhere else. More than a third of pts (35%) wished that their GI better understood the impact of UC on their quality of life (QoL). Pts and GIs generally agreed that the ability to perform daily activities and ability to control pain were among the most important aspects of UC management for pts (Table). While, globally, 71% of pts had set goals for managing their UC with their GI, this varied by country; highest in Australia (82%), Italy (82%) and Spain (84%) and lowest in the UK (51%). Only 58% of GIs discussed pts' lifestyle goals as part of UC management. Pts (62%) and GIs (72%) alike expressed a desire for greater discussion on goals. Conclusion: Pts and GIs agree that QoL and the ability to control pain are central to UC management. The importance of treatment goals is recognized by pts and GIs, with many pts identifying aspects important to them for managing their UC. Improved pt-to-GI communication should enable effective goal setting, and thus enhance pt experience and disease outcomes.